2006
DOI: 10.1295/polymj.pj2005223
|View full text |Cite
|
Sign up to set email alerts
|

Positive-type Alkaline Developable Photosensitive Branched Polyamides with Low Degree of Branching and Diazonaphthoquinone as a Photosensitive Compound

Abstract: ABSTRACT:A positive-type photosensitive polyamide based on the branched polyamides with low degree of branching and 1-{1,1-bis[4-(2-diazo-1-(2H)naphthalenone-5-sulfonyloxy)phenyl]ethyl}-4-{1-[4-(2-diazo-1-(2H)naphthalenone-5-sulfonyloxy)phenyl]methylethyl}benzene (S-DNQ) as a photosensitive compound has been developed. The branched polyamides with low degree of branching having amino end groups (2a and 2b) were prepared from a ABB 0 type monomer, 4-(2,4-diaminophenoxy) benzoic acid 1 in the presence of dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, the high functionality of the peripheral photosensitive groups is expected to produce high sensitivity toward exposure. Kakimoto et al 19 reported a positive-type photosensitive polyamide based on the branched polyamides with low degree of branching and S-DNQ as a photosensitive compound; it showed a sensitivity of 140 mJ cm À2 under 436 nm (g-line) light exposure. Tang et al 20 described a new route to hyperbranched polyarylenes (hb-PAs) that was functionality tolerant and regioselective.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high functionality of the peripheral photosensitive groups is expected to produce high sensitivity toward exposure. Kakimoto et al 19 reported a positive-type photosensitive polyamide based on the branched polyamides with low degree of branching and S-DNQ as a photosensitive compound; it showed a sensitivity of 140 mJ cm À2 under 436 nm (g-line) light exposure. Tang et al 20 described a new route to hyperbranched polyarylenes (hb-PAs) that was functionality tolerant and regioselective.…”
Section: Introductionmentioning
confidence: 99%